Molecular sieving carbon membranes and their use in separation processes.

JP7641469B2Active Publication Date: 2025-03-07FUNDACION TECNALIA RESEARCH & INNOVATION +1
View PDF 1 Cites -1 Cited by

Patent Information

Application Number
JP2022534635
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-11
Filing Date
2020-12-10
Publication Date
2025-03-07
Estimated Expiration
2040-12-10

AI Technical Summary

Benefits of technology

【0016】 驚くべきことに、実施例で示されるように、水飽和CMSMはガス混合物を用いて動作する場合には、外部の物質移動制限(濃度分極)による影響を受けない。したがって、一例として、ガス混合物中に存在する水素の分離では、水素分圧差及び水素流束の依存関係は、この混合物中のH2の濃度とは関係なく、ほぼ線形である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007641469000002
    Figure 0007641469000002
  • Figure 0007641469000003
    Figure 0007641469000003
  • Figure 0007641469000004
    Figure 0007641469000004
Patent Text Reader

Abstract

A water-saturated molecular sieving carbon membrane is provided by: (a) providing a hydrophilic molecular sieving carbon membrane (CMSM) containing pores with a pore size of 0.25 nm to 0.55 nm for molecular sieving and pores with a pore size of 0.55 nm to greater than 0.90 nm for adsorption / diffusion, and a negligible amount of pores greater than 0.90 nm, where the negligible amount of pores greater than 0.90 nm exists when a plot of N2 permeance versus permeation pressure at room temperature and a pressure of 1 to 4 bar has a zero or negative slope; and (b) humidifying the membrane until a water-saturated molecular sieving carbon membrane is obtained. A process for separating gases from gas mixtures using such a water-saturated membrane is also provided, as well as the use of the water-saturated membrane in solvent dehydration and as a membrane reactor.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of European Patent Application No. 19383095.7, filed December 11, 2019.

[0002] The present invention relates to the field of gas separation processes, and more particularly to a specific molecular sieve carbon composite membrane pretreated with water vapor and its use in gas separation processes, solvent dehydration and as a membrane reactor. [Background technology]

[0003] Membrane separation processes have relatively low energy requirements and low maintenance costs compared to other technologies. Two parameters characterize the separation performance of a membrane: permeability and selectivity.

[0004] Carbon molecular sieve membranes (CMSM) have been considered as the latest generation of membrane technology due to their uniform microporous structure. The main advantage of CMSM is that its pore size distribution (PSD) can be tailored to suit the desired separation. This distribution consists of pores of 0.5-2 nm (known as micropores or galleries) connected to smaller pores with sizes less than 0.7 nm (known as ultramicropores). The larger micropores provide higher permeability and sorption sites for strongly adsorbable molecules and at the same time reduce the passage of smaller adsorbed molecules (adsorption-diffusion mechanism). The ultramicropores are responsible for the separation by the molecular sieving mechanism, where only molecules with a size smaller than this pore can pass through. The combination of these two transport mechanisms provides the properties of high permeability and selectivity of these materials.

[0005] MALlosa et al. (Non-Patent Document 1) first reported the preparation of 3 μm thick, defect-free alumina-CMSM supported composites (Al-CMSM) on alumina tubes (200 nm pore size) using phenolic resins such as novolac and boehmite as precursors in a single soak-dry-carbonization cycle. The pore size and pore size distribution and the hydrophilicity of the pores were tuned by changing the carbonization temperature of the membrane (Non-Patent Document 2). Thus, they reported the effect of carbonization temperature on the pore size distribution and permeation properties of these Al-CMSMs carbonized at temperatures between 450 °C and 1000 °C. The properties such as selectivity and permeability of the membranes can also be controlled by adjusting the permeation temperature to change the amount of water adsorbed in the pores.

[0006] The separation of hydrogen, present in low concentrations in a mixture with methane, is interesting for the foreseen hydrogen economy. Hydrogen can be stored and distributed using the existing natural gas grid. For safety reasons, the hydrogen content in the distributed gas mixture must be low (around 10%). Moreover, hydrogen must be separated on-site at the end user.

[0007] Meanwhile, researchers continue to develop better processes, catalysts and adsorbents for increasing the efficiency of fuels and petrochemicals, which are heavily dependent on separation processes and their improvements. A suitable alternative to solve this problem is the development of membrane reactors. A membrane reactor (MR) is a device for carrying out reactions (steam reforming, dry reforming, autothermal reforming, methanol synthesis, etc.) and membrane-based separations simultaneously in the same physical device. Continuous extraction of one of these products shifts the equilibrium and increases the yield and selectivity compared to conventional systems.

[0008] In addition, since high concentrations of anhydrous solvents are of great importance in the chemical industry, effective dehydration processes continue to be developed, and in this regard, hydrophilic molecular sieving carbon membranes are very suitable candidates. Thus, there is a continuing need for better processes using CMSM that allow either obtaining higher purity in gas separation processes, and obtaining better efficiency in membrane reactors and solvent dehydration. [Prior art documents] [Non-patent literature]

[0009] [Non-Patent Document 1] Llosa MA et al.´´Composite-alumina-carbon molecular sieve membranes prepared from novolac resin and boehmite.Part I:Preparation, characterization and gas permeation studies´´, Int.J.Hydrogen Energy.2015,vol.40,pp.5653-5663. [Non-Patent Document 2] MALLosa et al.´´Composite-alumina-carbon molecular sieve membranes prepared from novolac resin and boehmite.Part II:Effect of the carbonization temperature on the gas permeation properties´´, Int.J.Hydrogen Energy.2015,Vol.40,pp.3485-3496. Summary of the Invention [Problem to be solved by the invention]

[0010] The inventors have found that pre-treating certain CMSMs with water vapor to obtain water-saturated membranes prior to carrying out a gas separation process significantly increases the selectivity of the membranes, and does so in a reproducible manner. Specifically, in water-saturated membranes, the filling of the pores with water helps to increase the permeability of adsorbable gases (adsorption-diffusion mechanism) and simultaneously increases the selectivity, while decreasing the permeability of non-adsorbable gases. [Means for solving the problem]

[0011] Thus, an aspect of the present invention is i) providing a hydrophilic molecular sieving carbon membrane (CMSM) comprising pores with a pore size of 0.25 nm to 0.55 nm for molecular sieving, and pores with a pore size of greater than 0.55 nm to 0.90 nm for adsorption-diffusion, and a negligible amount of pores greater than 0.90 nm, wherein the CMSM has a negligible amount of pores greater than 0.90 nm when a plot of N2 permeance versus permeation pressure at room temperature and a pressure of 1 to 4 bar has a zero or negative slope; ii) - by treating the CMSM with water vapor at 4 bar for a certain period of time, such as a period of 3 hours, after a further treatment with water vapor, by treating the CMSM with water vapor at a temperature between 5°C and 180°C, at atmospheric pressure and at a relative humidity higher than 95%, for example 99%, for a certain period of time, such that at temperatures between 5°C and 180°C the permeation flux of non-adsorbable gases, such as N2 or He, is constant; or Alternatively, it relates to a water-saturated molecular sieving carbon membrane obtained by humidifying the CMSM prepared in step i) to obtain water-saturated CMSM by exposing the CMSM to a water-saturated N2 or He gas stream by bubbling the gas into a tank filled with water at the mentioned temperature such that the permeation flux of the non-adsorbable gas such as N2 or He is constant at 4 bar and at a temperature between 5°C and 180°C during a certain period of time, such as a period of 3 hours.

[0012] The CMSM used in step i) comprises pores of a certain pore size as defined herein and a "defect-free structure", i.e. a structure that does not exhibit defects that may affect the gas separation properties of the membrane (i.e. the membrane permeance and selectivity). A CMSM containing the highest of these pore sizes is considered to be "defect-free" if it has a negligible amount of pores larger than 0.90 nm, i.e. a plot of N2 permeance against permeate pressure at room temperature and a pressure between 1 and 4 bar has a zero or negative slope. The combination of these features, i.e. having pores of the mentioned pore size and the absence of defects in the porous structure, makes it possible to obtain the desired effect when humidifying the CMSM as defined in step ii).

[0013] Another aspect of the present invention relates to a process for preparing a water-saturated molecular sieving alumina-carbon composite membrane (water-saturated Al-CMSM), the process comprising: i) hydrophilic Al-CMSM, providing a porous α-Al2O3 support, preparing a solution containing 5-20% by weight of phenol formaldehyde resin, 0.5-5% by weight of formaldehyde, 0.1-2% by weight of ethylenediamine, 0.1-5% by weight of boehmite in N-methyl-2-pyrrolidone, and carrying out a prepolymerization process by heating the solution (e.g., 80-110°C, 30 minutes to 3 hours) to obtain a coating solution; - dip-coating a porous α-Al2O3 support in a coating solution to obtain a coated support; drying the coated substrate at a temperature of 70-120°C to complete the polymerization process; carbonizing the dried coated support at a carbonization temperature of 450°C to 750°C to obtain -Al-CMSM; ii) humidifying the Al-CMSM prepared in step i); - treating the Al-CMSM with water vapor at 4 bar for a certain period of time, such as a period of 3 hours, after a further treatment with water vapor; by treating the Al-CMSM with water vapor at a temperature between 5°C and 180°C, at atmospheric pressure and at a relative humidity higher than 95%, for example 99%, for a certain period of time, such that at temperatures between 5°C and 180°C the permeation flux of non-adsorbable gases, such as N2 or He, is constant; or Alternatively, after further exposure to a water-saturated N2 or He gas stream, humidifying the Al-CMSM prepared in step i) to obtain water-saturated Al-CMSM by exposing the Al-CMSM to a water-saturated N2 or He gas stream by bubbling the gas into a tank filled with water at the mentioned temperatures such that the permeation flux of non-adsorbable gases such as N2 or He is constant at temperatures between 5°C and 180°C at 4 bar during a certain period of time, such as a period of 3 hours.

[0014] Another aspect of the present invention is the water saturated Al-CMSM obtained by the above defined process.

[0015] Another aspect of the invention relates to a process for separating a gas from a gas mixture, the process comprising: a) providing a water-saturated membrane as defined herein above and below; b) providing a gas mixture comprising at least two gases; c) feeding the gas mixture to a water-saturated CMSM at a temperature between 5°C and 300°C to obtain a retentate and a permeate, the feeding being carried out at a pressure such that the partial pressure of the gas in the retentate is higher than the partial pressure of the gas in the permeate and a difference in permeation is observed when compared to an identical CMSM that has not been subjected to a humidification step in order to obtain a water-saturated membrane at the feed temperature and feed pressure. Effect of the Invention

[0016] Surprisingly, as shown in the examples, water-saturated CMSM is not affected by external mass transfer limitations (concentration polarization) when operating with gas mixtures. Thus, as an example, for the separation of hydrogen present in a gas mixture, the dependence of hydrogen partial pressure difference and hydrogen flux is approximately linear, independent of the concentration of H2 in this mixture.

[0017] Another aspect of the present invention relates to the use of water-saturated CMSM as defined herein above and below for separating gases from a gas mixture.

[0018] The inventors have also recognised that water-saturated CMSM as defined herein above and below is also useful for the dehydration of organic solvents and as a membrane reactor, and therefore these uses also form part of the present invention. [Brief description of the drawings]

[0019] [Figure 1] Micropore size distributions of carbon membranes carbonized at a) 450° C. and 650° C., b) 550° C. and 750° C. MS: molecular sieve region, AD: adsorption-diffusion region. [Diagram 2] These represent the changes that CMSM undergo: i) during carbonization, functional groups are removed, leaving activated carbon groups capable of reacting with active molecules; whereby, ii) water is chemisorbed (i.e., the active atoms react with water), resulting in oxygen-containing functional groups and generating hydrophilic pores; whereby, iii) the hydrophilic groups are capable of absorbing water that physically fills the pores, reducing the pore size. [Figure 3a] N2 permeation is shown with a pressure difference of 400 kPa and a heating time of 0.7°C per minute. [Figure 3b] N2 permeation is shown with a pressure difference of 400 kPa and a heating time of 0.7°C per minute. [Figure 4a] 3 shows the derivative curves of the polynomial fitting of the flux from FIG. 3a. [Figure 4b] 3 shows the derivative curves of the polynomial fitting of the flux from FIG. 3b. [Diagram 5]Figure 1 shows the N2 and H2 permeance of Al-CMSM carbonized at 600 °C before and after humidification (outside the reactor). [Figure 6] 1 shows the permeation results of H2 and CH4 for the dried CMSM-550 and CMSM-600 membranes obtained in Example 3 at 20° C. using Robeson upper limit plots, respectively. [Figure 7] Figure 1 shows a comparison of hydrogen permeation flux for a 50% H2-50% CH4 mixture using dry (after water desorption at 150°C) or humidified (wet) CMSM-550 membranes. Permeation temperature: 20°C. [Figure 8] Figure 1 shows a comparison of the hydrogen purity of the permeate obtained by permeating a 50% H2-50% CH4 mixture through dry (after desorption at 150°C) and humidified (wet) CMSM-550 membranes. Permeation temperature: 20°C. [Figure 9] 1 shows a comparison between the hydrogen fluxes of two H2-CH4 mixtures containing 10% hydrogen and 50% hydrogen, respectively, at 20°C, 35°C, 50°C, and 70°C in a humidified CMSM-550 membrane. [Figure 10] FIG. 1 shows a comparison of the hydrogen purity of the permeate obtained by permeating two H2-CH4 mixtures containing 10% hydrogen and 50% hydrogen, respectively, at 20° C., 35° C., 50° C., and 70° C. using a humidified CMSM-550 membrane. [Figure 11] 1 shows a comparison between the hydrogen fluxes permeating two H2-CO2 mixtures containing 10% hydrogen and 50% hydrogen, respectively, through a humidified CMSM-550 membrane at 20°C, 35°C, and 50°C. [Figure 12] FIG. 1 shows a comparison of the hydrogen purity of the permeate obtained by permeating two H2-CO2 mixtures containing 10% hydrogen and 50% hydrogen, respectively, through a humidified CMSM-550 membrane at 20° C., 35° C., 50° C. and 70° C. [Figure 13] 1 shows a comparison between the hydrogen fluxes of two H2-N2 mixtures containing 10% hydrogen and 50% hydrogen, respectively, at 20° C., 35° C., 50° C., and 70° C. in a humidified CMSM-550 membrane. [Figure 14] FIG. 1 shows a comparison of the hydrogen purity of the permeate obtained by permeating two H2-N2 mixtures containing 10% and 50% hydrogen, respectively, at 20° C., 35° C., 50° C., and 70° C. using a humidified CMSM-550 membrane. [Figure 15] 1 shows a comparison between the hydrogen fluxes of two H2-CH4 mixtures containing 10% hydrogen at 20°C, 50°C, 70°C and 100°C in dry and humidified CMSM-600 membranes. [Figure 16] FIG. 1 shows a comparison of permeate hydrogen purity obtained by permeating two H2-CH4 mixtures containing 10% hydrogen at 20° C., 50° C., 70° C. and 100° C. using dry and humidified CMSM-600 membranes. [Figure 17] The relative increase in purity obtained with humidified membrane conditions is shown. [Figure 18] An example of the effect of flux on partial pressure difference for a Pd-based membrane (flux ≈ ΔP 0.5) and an Al-CMSM (flux is proportional to ΔP) considering that they have the same permeance (mol m-2s-1 Pa-1) at a pressure of 1 bar is shown. [Figure 19] Hydrogen flux permeation of H2 / CH4 binary mixtures at 400 °C for H2 purities between 100 and 50% by volume as a function of the square root difference of H2 partial pressures on the retentate (on average) and permeate sides of a PdAg support membrane. [Figure 20] 1 shows the hydrogen flux at different hydrogen concentrations in the inlet mixture of H2-CH4 tested at 400° C. for a PdAg supported membrane. [Figure 21] 4 shows the hydrogen purity at different hydrogen concentrations in the inlet mixture of H2-CH4 tested at 400° C. for a PdAg supported membrane. [Figure 22] Hydrogen flux as a function of hydrogen % in mixtures of H2 / N2, H2 / CO2 and H2 / CH4 at 400 °C, 3 bar total pressure and vacuum on the permeate side for a PdAg supported membrane. [Figure 23] 1 shows the hydrogen flux as a function of hydrogen partial pressure difference for various H2 / CH4 mixtures at an operating temperature of 20° C. when the CMSM-550 was tested after exposure to ambient humidity. [Figure 24] a) Schematic diagram of hydrophilic pores filled with water, b) Water permeance at various temperatures and pressures for Al-CMSM of Example 2.2 carbonized at 550° C. [Diagram 25] FIG. 13 shows the water permeability of Al-CMSM of Example 2.2 carbonized at different temperatures at various temperatures and a pressure difference of 3 bar. [Figure 26] FIG. 2 shows the water gas selectivity over various gases in function of permeation temperature for Al-CMSM of Example 2.2 carbonized at different temperatures. Detailed Description of the Invention

[0020] All terms used herein are to be understood in their ordinary meaning known in the art unless otherwise specified. Other, more specific definitions for terms used in this application are set forth below. Also, this definition is intended to be applied uniformly throughout the specification and claims, unless otherwise expressly stated that the definition provides a broader definition.

[0021] The term "permeation flow" is defined as the volume of gas passing through a membrane per unit time. This value is determined experimentally using a soap film flowmeter.

[0022] The term "permeation flux" is defined as the volume flowing through a membrane per unit area per unit time. This value is calculated by dividing the "permeate flow" by the area of ​​the membrane.

[0023] The term "permeance" is defined as the volume of feed gas passing through unit area of ​​membrane per unit time under unit pressure gradient. The common unit used in CMSM is mol m -2 s -1 ·Pa -1 This value is calculated by dividing the "permeate flux" by the pressure difference between the retentate and the permeate.

[0024] The term "permeability" is defined as the flux of a substance moving through a membrane per unit driving force per unit membrane thickness.

[0025] The term "perm-selectivity" or ideal selectivity for a gas refers to the ratio of the permeances of two gases at the same temperature.

[0026] The term "composite alumina-carbon molecular sieve membrane" or "Al-CMSM" refers to a carbon membrane having alumina nanoparticles dispersed within a carbon matrix.

[0027] The term "water-saturated CMSM" or "hydrated CMSM" refers to a CMSM (including supported Al-CMSM) containing an amount of water corresponding to this state, which would contain CMSM treated with water vapor at a temperature between 5°C and 180°C, such as room temperature, at atmospheric pressure, for a period of time, such that the permeation flux of non-adsorbable gases, such as N2 or He, at 4 bar, at a temperature at which the CMSM is treated with water vapor, is constant during a certain period of time, such as a period of 3 hours. Alternatively, "water-saturated CMSM" may be obtained by exposing CMSM to a water-saturated N2 or He gas stream by venting the gas into a tank filled with water at the mentioned temperature, such as room temperature, such that the permeation flux of non-adsorbable gases, such as N2 or He, at 4 bar, at a temperature between 5°C and 180°C, is constant during a certain period of time, such as a period of 3 hours.

[0028] Generally, especially at temperatures higher than 180° C., water-saturated CMSM will contain CMSM that has been subjected to a wetting treatment carried out at the temperature and pressure at which the permeation is carried out, with the aim of filling the pores with water until they no longer hold water, and will contain at least a certain amount of water corresponding to this state, such that a difference in permeation is observed due to the presence of water in the pores, when compared to an identical CMSM that has not been subjected to such a wetting process.

[0029] The term "hydrophilic CMSM" refers to a CMSM with a N2 permeance of 7×10 at 300 °C and 4 bar pressure difference before being humidified to obtain water-saturated CMSM. -9 mol m 2 s -1 ·Pa -1 After being humidified to obtain a water-saturated CMSM, the N2 permeance at room temperature and 1 bar pressure difference is 1×10 -9 mol m 2 s -1 ·Pa -1 It is a CMSM that is lower than

[0030] Membrane processes are characterized by the fact that a feed stream, which is a gas mixture, is split into two streams: retentate and permeate. The retentate is the portion of the feed that does not pass through the membrane, while the permeate is the portion of the feed that does pass through the membrane (i.e., the separated gas). To separate a gas from a gas mixture, the partial pressure of the gas in the retentate must be higher than the pressure of the permeate.

[0031] Therefore, the permeation of a desired gas depends on the partial pressure difference between the gas in the retentate and the gas in the permeate. For example, for a feed that is a mixture of 10% H2 and 90% CH4, if the pressure in the permeate is atmospheric pressure (1 bar), the pressure in the feed must be higher than 10 bar. This means that the partial pressure of H2 in the feed must be higher than 1 bar.

[0032] The term "pressure difference" refers to the difference between the gas pressure in the retentate and the gas pressure in the permeate.

[0033] For a given gas, the term "partial pressure difference" refers to the difference between the partial pressure of the gas in the retentate and the partial pressure of the gas in the permeate.

[0034] The term "negligible" refers to values ​​that are either equal to 0 or below a defined threshold within the context of measurement accuracy. These are, for example, considerations of deviations from 0, which are largely unavoidable for structural reasons, or which have no significant effect on performance in terms of permeance and selectivity of the CMSM. To verify whether a CMSM has a "negligible amount of pores larger than 0.90 nm", i.e., whether it has a defect-free structure, the CMSM must be capable of presenting a plot of N2 permeance versus permeation pressure at room temperature and pressures between 1 and 4 bar, with a zero or negative slope.

[0035] The term "room temperature" refers to a temperature of about 20°C to about 25°C.

[0036] The term "atmospheric pressure" as used herein refers to atmospheric pressure substantially equal to 101.325 kPa (ie, 760 mmHg) ± 15 kPa.

[0037] As used herein, the terms "%" or "concentration" of a gas component in a gas mixture refers to the amount by volume of a single component of gas relative to the total volume of the gas mixture, or, if specifically mentioned, the amount by volume of one or more other gas components in the gas mixture.

[0038] As used in this specification and the appended claims, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise.

[0039] As mentioned above, the present invention relates to water-saturated carbon molecules as defined above.

[0040] These carbon membranes exhibit a porous structure where the permeation mechanism is the result of molecular sieving (pore range: 0.25-0.55 nm) and / or surface diffusion (0.5-0.90 nm). CMSMs, such as Al-CMSMs, are produced by carbonizing polymer precursors at temperatures of, for example, 250°C-2500°C, or 450°C-1500°C, especially 500°C-800°C, under inert atmosphere or vacuum (see Llosa MA et al. (Part I) 2015; Campo MC et al. 2010). Examples of polymer precursors include, but are not limited to, polyimides, polyfurfuryl alcohol, phenolic resins, cellulose, cellulose derivatives, and poly(vinylidene chloride). Phenolic resins, such as resole and novolac resins, are desirable precursors for preparing CMSMs because they present the advantage of being inexpensive, have high carbon yields, and can withstand high temperatures without losing their shape.

[0041] Phenolic resins are the product of the polycondensation reaction of phenol with formaldehyde, and their structure and properties depend on the formaldehyde / phenol ratio (F / P), catalyst, pH and temperature. Phenolic resins exist in two forms: resole and novolac. Resole resins are the product of basic catalysis with a predominance of formaldehyde (F / P>1). Novolac resins are obtained in acidic medium and have a lower amount of formaldehyde than resole resins, usually with respect to F / P of about 0.75-0.85.

[0042] In one embodiment of the disclosed process for the preparation of water-saturated Al-CMSM and the water-saturated Al-CMSM obtained by this process, the phenol formaldehyde resin is a novolac resin.

[0043] In another embodiment of the process for the preparation of Al-CMSM and water-saturated Al-CMSM obtained thereby according to the present disclosure, optionally in combination with one or more features of the particular embodiments defined above, the carbonization temperature is between 450°C and 700°C, in particular between 500°C and 650°C, e.g. 550°C or 600°C.

[0044] Prior to carbonization, for self-supporting membranes the polymer precursors are shaped (e.g. films, hollow fibers) and for supported membranes these are typically produced by immersing (coating) a porous support in a solution containing the polymer precursor.

[0045] As mentioned above, the humidification of the membrane is has been treated with water vapor at a temperature between 5°C and 180°C (such as, for example, 20°C, 25°C, 40°C, 70°C, 100°C or 120°C), at atmospheric pressure and at a relative humidity higher than 95% (in particular 99%), such that, after further treatment with water vapor, the gas permeation flux at the temperature at which the CMSM is treated with water vapor at 4 bar is constant for a non-adsorbable gas, such as, for example, N2 or He, during a certain period of time, such as, for example, a period of 3 hours, - after further exposure to a gas stream saturated with water, venting the gas to a tank filled with water at the mentioned temperature such that the permeation flux of a non-adsorbable gas, e.g. N2 or He, at 4 bar and at a temperature between 5°C and 180°C (e.g. 20°C, 25°C, 40°C, 70°C, 100°C, or 120°C, etc.) is constant during a certain period, e.g. a period of 3 hours, in order to obtain a CMSM containing at least a certain amount of water, which corresponds to this state, which will contain the CMSM that has been exposed to the gas stream saturated with water.

[0046] The permeate flux was measured using a soap film rheometer at the stated temperature and pressure.

[0047] In another embodiment of the water-saturated molecular sieving carbon membrane of the present invention, optionally in combination with one or more features of the particular embodiments defined above, at a temperature higher than 180° C. (such as, for example, 200° C., 250° C. or 300° C.), humidification of the membrane is carried out to obtain a CMSM containing at least a certain amount of water, corresponding to this state, which would contain a CMSM that has been subjected to a humidification treatment carried out at the temperature and pressure at which the permeation is carried out, with the aim of filling the pores with water until they no longer hold water, so that a difference in permeation is observed due to the presence of water in the pores, when compared to an identical CMSM that has not been subjected to such a humidification process.

[0048] In one embodiment, the humidification of the membrane is carried out at room temperature, atmospheric pressure and a relative humidity higher than 95%, such as 99%, for a period of time such that the gas permeation flux at the temperature at which the CMSM was treated with water vapor is constant for a non-adsorbable gas, such as N2 or He, for a certain period of time, such as a period of 3 hours, at 4 bar.

[0049] In one embodiment of the water-saturated molecular sieving carbon membrane of the present invention, optionally in combination with one or more features of the specific embodiments defined above, the CMSM is a molecular sieving alumina-carbon composite membrane (Al-CMSM), in particular having a nitrogen content of 0.1% to 4.0% by weight, an alumina content of 2.5% to 50% by weight, and a carbon content of 50% to 95% by weight, relative to the total weight of the membrane.

[0050] Al-CMSM can be prepared using a single soak-dry carbonization method on a porous alumina support as described in several materials and in Llosa MA et al (Part I) 2015 (see experimental section on p.5655), except that the carbonization temperature is chosen arbitrarily. Other examples of Al-CMSM are disclosed in, for example, Teixeira et al. 2011, Teixeira et al. 2012, Rodrigues et al. 2014.

[0051] Pore ​​size characteristics The pore size and pore size distribution of the molecular sieving carbon membrane were calculated using data obtained from the CO2 adsorption equilibrium at 0 °C. The CO2 adsorption equilibrium isotherm was measured to an accuracy of 10 -5 The pore size distribution of CMSM was determined gravimetrically using a Rubotherm hanging magnetic balance in mg. Details on how to determine the pore size distribution of CMSM can be found in Nguyen C. and Do, DD 1999, and Nguyen C., et al. 2003. To obtain water-saturated CMSM, pretreatment of the membrane with water vapor can be performed inside or outside the permeation device.

[0052] Pretreatment with water vapor outside the permeator To obtain a water-saturated CMSM, a hydrophilic CMSM as defined above is introduced into a closed vessel in the presence of water at a temperature of 5-180°C, e.g. 5-120°C, in particular at room temperature, and at a relative humidity higher than 95%, e.g. 99%, in order to fill the pores with water until they no longer hold any more water.

[0053] To know when the membrane is saturated with water, the gas permeation flux of the membrane at a mentioned temperature, e.g. room temperature, at 4 bar is monitored until it becomes constant during a certain period, e.g. a period of 3 hours. The gas used is a non-adsorbing gas at the permeation temperature (e.g. room temperature), e.g. N2 or He.

[0054] Pretreatment with water vapor inside the permeation device As an alternative method to obtain water-saturated CMSM, the CMSM is introduced into a permeator which is fed, preferably at room temperature, with (i) a gas stream saturated with water, e.g. obtained by bubbling the gas stream through a tank filled with water before feeding the CMSM to the permeator, or (ii) water vapor or a mixture of gases containing water. The treatment time can be from one minute to several hours.

[0055] After treatment, the gas flux of 4 bar of non-adsorbable gas (i.e., N2 or He) is measured. The treatment and gas permeation cycle is repeated until the gas permeation is constant over a period of 3 hours.

[0056] Uses of the Water-Saturated CMSM of the Present Invention As mentioned above, the present invention also relates to a process for separating gases in a gas mixture by using a water-saturated CMSM as defined above, which has some specific features.

[0057] Thus, a CMSM having some special features such as pore size, pore size distribution and hydrophilicity is subjected to a humidification pretreatment (at permeation conditions of pressure and temperature) until it is saturated with water. A gas mixture, comprising at least two gases, is fed to the water-saturated CMSM at a pressure such that the partial pressure of the gas in the retentate is higher than the partial pressure of the gas in the permeate and the membrane is still water-saturated. That is to say, a difference in permeation is observed when compared to an identical CMSM that was not subjected to a humidification step to obtain a water-saturated membrane at the feed temperature and feed pressure. This process can be carried out at temperatures between 5°C and 300°C.

[0058] In an embodiment, optionally in combination with one or more features of the particular embodiments defined above, step (c) is carried out at a temperature between 5° C. and 250° C., between 5° C. and 120° C., between 15° C. and 120° C., between 15° C. and 100° C., between 15° C. and 70° C., or between 20° C. and 50° C., such as for example 40° C. In a particular embodiment, step (c) is carried out at room temperature.

[0059] Gases in pure or mixed form can be fed to the permeation device by digital mass flow controllers, while the pressure can be controlled using a digital back pressure regulator. The maximum pressure of the retentate can be, for example, 40 bar, while the permeate can be operated at different pressures, up to vacuum (using a vacuum pump). Several thermocouples can be used to record the temperature profile following the permeation device.

[0060] Gas separation in the disclosed hydrophilic membranes is based on molecular sieving (MS, gases smaller than the pores permeate) and adsorption-diffusion (AD, differences in affinity between the gas and water present in the pores). The pores of the disclosed CMSM are divided into two groups (Figure 1: a) pores with pore sizes between 0.25 nm and 0.55 nm, where the separation is due to molecular sieving, and b) pores with pore sizes larger than 0.55 nm and 0.90 nm, where water is adsorbed). In the AD region, water adsorbed in the pores reduces the size of the pores, and the amount of adsorbed water varies with temperature, which in turn varies the pore size with the amount of water. Gases pass according to their size (smallest gases pass faster), and gases that interact (adsorb) more with water in the pores (more adsorbed gases) preferentially permeate. The interaction with water varies with the polarity of the gas, and gases with a dipolar moment (i.e. water) have a higher permeability. If the gas is not polar, then gases with higher polarizability will permeate faster (eg, CO2 and H2 rather than He).

[0061] [Table 1]

[0062] The polarizability of an atom or molecule is a measure of the ease with which electrons and nuclei can be displaced from their average positions and form an instantaneous dipole. The kinetic diameter represents the likelihood that a molecule in a gas will collide with another molecule. It is an indication of the size of the molecule as a target. The polarizability and kinetic diameter of gases can be found in chemical and physical data handbooks.

[0063] In another embodiment, optionally in combination with one or more features of the specific embodiments defined above, the at least two gases have polarizabilities between 2 and 27, or between 2 and 26.3, and at least one of the at least two gases has a kinetic diameter of less than 0.55 nm. If three or more gases have kinetic diameters smaller than 0.55 nm, the separation is determined by a difference in polarizability between the at least two gases of 1 nm or more if the difference in kinetic diameter between the at least two gases is 0.01 nm or more. 3 This occurs when the above conditions are met, or when both conditions are met.

[0064] In particular, the at least two gases are selected from the group consisting of He, H2O, Ne, H2, NO, Ar, NH3, N2, O2, CO2, CO, CH4, C2H4, C2H6, propene, C3H8 (propane), H2S, methanol, ethanol, propanol, dioxane, dimethylformamide, dimethylsulfoxide, acetone, and N-methyl-2-pyrrolidone. Examples of gases with a kinetic diameter greater than 0.55 nm are n-butane or isobutane. Examples of solvents with a kinetic diameter greater than 0.55 nm are CHCl3, CHCl2, methanol, ethanol, dimethyl ether, dimethyl carbonate, acetone, acetonitrile, dioxane. In particular, the at least two gases are mixtures selected from the group consisting of H2 / CH4, H2 / N2, H2 / CO2, CO2 / CH4, CO2 / N2, O2 / N2, and biogas.

[0065] In a particular embodiment, optionally in combination with one or more features of the particular embodiments defined above, the gas mixture comprises 5%-20% H2 and 95%-80% CH4, in particular about 10% H2 and about 90% CH4, in which case step c) is carried out at a hydrogen partial pressure difference of 3 bar or more, such as 3-8 bar, and at a temperature of 40° C. or less, such as 20° C. or room temperature.

[0066] Advantageously, unlike other known processes, the water-saturated CMSM of the present invention allows for the separation of H from its mixture with CH at low temperatures. As a result, the purity of the permeate is increased.

[0067] In a particular embodiment, optionally in combination with one or more features of the particular embodiments defined above, the at least two gases are CO2 and N2. In particular, the gas mixture comprises 10%-20% CO2 and 65%-75% N2, in particular about 15% CO2 and 70% N2.

[0068] In a particular embodiment, optionally in combination with one or more features of the particular embodiments defined above, the at least two gases are H2 and CO2. In particular, the gas mixture comprises 55%-65% H2 and 30%-40% CO2, more particularly about 60% H2 and 35% CO2.

[0069] In another embodiment, optionally in combination with one or more features of the particular embodiments defined above, the gas mixture is anhydrous.

[0070] In another embodiment, optionally in combination with one or more features of the particular embodiments defined above, the gas mixture comprising at least two gases is biogas and CO2 is removed from the biogas.

[0071] As mentioned above, another aspect of the present invention relates to the use of water-saturated CMSM as defined herein above for separating gases from a gas mixture.

[0072] Biogas is a gas mixture produced by the decomposition of organic matter without oxygen (anaerobic) and containing methane and carbon dioxide. In particular, biogas is a gas mixture containing mainly methane and carbon dioxide, with small amounts of other gases, e.g. H2, H2S, N2, and water vapor. The use of biomethane is preferred over biogas, as it increases the energy density of the fuel source. It can be used directly in all existing installed plants and can also be fed into the natural gas grid.

[0073] In another embodiment, the use of water saturated CMSM is for the purpose of biogas upgrading (i.e., to remove CO2 from biogas).

[0074] In another embodiment, the use of water saturated CMSM is for the removal of CO2 from a gas mixture containing at least 50% nitrogen, particularly the gas mixture containing 5%-10% CO2 and 65%-75% N2, more particularly about 5% CO2 and about 70% N2.

[0075] In another embodiment, the use of water saturated CMSM is for the separation of H2 from gas mixtures further comprising CO2, in particular from the products of pre-combustion after the water gas shift reaction, where the gas mixture is 50-70% H2 and 50%-30% CO2, or for the separation of alkanes from alkenes, such as C2H6 from C2H4, for example in a gas mixture comprising 30-70% C2H4 and 70-30% C2H6, or for the separation of propane from propene, for example in a gas mixture comprising 30-70% propene and 70%-30% propane, or for the separation of propane, propene or mixtures thereof from butane, for example in a gas mixture comprising 70%-30% propane, propene or mixtures thereof and 30%-70% butane.

[0076] As mentioned above, another aspect of the present invention relates to the use of water-saturated CMSM as defined herein above for the dehydration of a solvent, i.e. removing water from an organic solvent to obtain an organic solvent containing 0.1-1% water. Examples of organic solvents include methanol, ethanol, propanol, n-butanol, isobutanol, tert-butanol, acetone, dimethyl ether, dimethyl carbonate, tetrahydrofuran, acetonitrile, dioxane, acetic acid and ethyl acetate.

[0077] In the solvent dehydration process, gas is passed through the pores by applying a vacuum from the permeate side of the membrane. For molecular sieves (>0.55 nm), only water passes through because the solvent molecules are larger than or close to the largest pores and water is very small. In addition, water is preferentially adsorbed in the hydrophilic pores in the AD region of the pores, blocking the passage of other smaller hydrophilic molecules. Dipolar protic solvents are used in organic synthesis and dissolving polymers, but very small or trace amounts of water in these solvents can be harmful.

[0078] As mentioned above, another aspect of the present invention relates to the use of the water-saturated CMSM as defined above of the present invention as a membrane reactor. The water-saturated CMSM of the present invention can be used for process intensification of in-situ water removal during catalytic reactions in the chemical, petrochemical, food and cosmetic fields. In particular in the production processes of methane, methanol, dimethyl ether, dimethyl carbonate (DMC) or other organic solvents, water is produced during the reaction. Examples of processes in which the water-saturated CMSM of the present invention can be used as a membrane reactor include the reaction of CO2 and H2 to produce CH4, the synthesis of esters by reaction of alcohols with carboxylic acids, biodiesel fuels and biolubricants, methanol produced from CO2 and H2, dimethyl ether obtained by dehydration of methanol or direct synthesis from CO2 and H2, and the synthesis of dimethyl carbonate from CO2 and methanol. By using the water-saturated CMSM of the present invention, water is removed from the reaction products, for example for the production of compounds of interest such as oxidized solvents and esters.

[0079] The water-saturated CMSM of the present invention is easier and cheaper to prepare and has better permeation properties, especially for CO2 and H2 reactions, than the zeolite membranes currently being investigated in the membrane reactor field.

[0080] As mentioned above, one aspect of the present invention relates to a process for the preparation of water-saturated Al-CMSM as defined above. The water-saturated Al-CMSM obtained by the above-mentioned process also forms part of the present invention.

[0081] Thus, the process for separating a gas from a gas mixture of the present invention can also be defined as comprising the following steps, namely: a) providing a water saturated Al-CMSM as defined herein above; b) providing a gas mixture comprising at least two gases as defined above; c) providing a gas mixture to the water-saturated Al-CMSM at a temperature between 5° C. and 300° C., in particular between 5° C. and 250° C., at a pressure such that the partial pressure of the gas in the retentate is higher than the partial pressure of the gas in the permeate, to obtain a retentate and a permeate.

[0082] Throughout the specification and claims, the term "comprises" and variations of this term are not intended to exclude other technical features, additives, ingredients, or steps. Furthermore, the term "comprises" encompasses the instances of "consisting of." Additional objects, advantages, and features of the present invention will become apparent to those skilled in the art upon review of this description or may be learned by practice of the present invention. The following examples and figures are provided by way of illustration and are not intended to limit the present invention. Moreover, the present invention covers all possible combinations of the specific and preferred embodiments described herein. EXAMPLES

[0083] Example 1. Preparation of membrane Several Al-CMSMs were prepared using a single soak-dry carbonization method on a porous alumina support as described in several materials and in Llosa MA et al. (Part I), (see the Experimental section in p.5655), with the exception of the carbonization temperature. In particular, this document discloses the preparation of Al-CMSMs by performing carbonization of the membrane at 500°C. Similarly, Al-CMSMs were prepared at 500°C, 550°C, 600°C, 650°C, 750°C, 850°C, and 1000°C.

[0084] Since the permeation depends on humidity and storage time (fluctuations in the water content of the pores), the effectiveness of pretreatment of CMSM with Al-water vapor was demonstrated by comparing the performance with that of a "dry membrane" obtained by removing most of the water present in the pores by heat treatment. The water-saturated Al-CMSM after pretreatment with water vapor is named the "humidified membrane."

[0085] Micropore Size Distribution The micropore size distribution of the membranes carbonized at various temperatures is presented in Figure 1. The membranes show the presence of ultramicropores (0.25 nm-0.55 nm range, MS region) and larger micropores (0.55 nm-0.90 nm, AD region). The membrane carbonized at 450 °C has a small volume of pores with pores in the 0.4 nm-0.90 nm range, while the membrane carbonized at 550 °C has a similar pore size distribution pattern but a significantly larger pore volume. When carbonized at 650 °C, a bidisperse pore size distribution with a significantly larger volume in the MS range (0.25-0.55 nm, AD region, with the majority of the pores in the range larger than 0.55-0.65 nm) provided a good compromise between selectivity and permeability. Finally, compared to 650°C, the 750°C sample shows smaller volumes in the MS region and larger volumes in the AD region with a well-defined pore size distribution, which may contribute to the higher permeability. These results indicate that as the carbonization temperature increases in volume, the number of smaller micropores increases up to 650°C, forming larger pores at higher carbonization temperatures.

[0086] Permeation Test A shell-and-tube setup equipped with a back pressure regulator (lower limit <20 kPa) and a soap film flowmeter (detection limit <0.2 mL / min) was used to measure the gas permeability through the supported CMSM. The selected gas was introduced into the membrane tube from the outer shell and the gas permeated through the membrane was directed to the soap film flowmeter to determine the flow rate. Gas permeability to N2 was determined at room temperature and different pressures (unless otherwise stated), with the permeate side at atmospheric pressure.

[0087] Hydrophilicity and water adsorption in pores Immediately after carbonization, the N2 permeance of the membrane was measured while avoiding contact with air.

[0088] During carbonization, functional groups are removed, leaving activated carbon groups that can react with active molecules, as shown in Figure 2. This allows water to chemisorb to oxygen-containing functional groups, creating hydrophilic pores. Moreover, the hydrophilic groups can absorb water that physically fills the pores, reducing the pore size.

[0089] Water desorption of membranes carbonized at various temperatures was investigated by measuring the permeation of N2 at a pressure difference of 400 kPa in function of the permeation temperature (Figures 3a and 3b). In Figure 3a, it can be observed that the N2 flux increases as the carbonization temperature of the membrane increases from 450 to 600 °C. At 450 °C, the N2 flux is low and there is no maximum. This indicates that the low carbonization temperature hardly formed any pores. The derivative curves of flux and permeation temperature from Figures 3a and 3b are presented in Figures 4a and 4b, respectively. The derivative intensity corresponding to the maximum value and the intensity of the permeation temperature increase with the carbonization temperature, and the maximum value shifts with the carbonization temperature. In this case, the carbonization temperatures are 500 °C, 550 °C, and 600 °C, and the maximum temperatures are 150 °C, 175 °C, and 280 °C, respectively. This behavior is related to the strength of the interaction of water with the pores. At 750 and 850 °C, the N2 permeability was low and no maximum was observed. At these temperatures, the pores become less hydrophilic. It can be inferred that, especially at the carbonization temperatures tested at about 600-650 °C, the membrane has the highest hydrophilicity and traps more water in the pores.

[0090] For the membrane carbonized at 500°C, the system was cooled to room temperature without removing the membrane from the permeation reactor, a boat containing water was introduced, and the N2 permeance at 400 kPa was recorded as a function of time. At the beginning of the experiment, a sharp decrease in permeance was observed. Water is adsorbed at the most accessible points of the membrane. Adsorption is rapid for the first 20 minutes, after which a slow and slight decrease is observed in permeance, water being adsorbed in the internal pores of the membrane. Thus, the increase in nitrogen permeance at temperature in Figure 3 is the result of the slow removal of water from the pores. The same membrane was treated again at 300° under nitrogen to remove the physisorbed water from the pores. The N2 permeance with time was measured as described above, but this time a boat containing hexane was introduced into the reactor. The N2 permeance remained constant, clearly indicating that the membrane pores are hydrophilic (i.e., hexane is hydrophobic and does not adsorb in the pores).

[0091] Example 2. Pretreatment of Al-CMSM with water vapor outside the permeation device 2.1 Dry membrane To remove the adsorbed water from the pores, the Al-CMSM carbonized at 500 °C was heated at 200 °C under N2.

[0092] 2.2 Humidifying membrane The dried Al-CMSM prepared as disclosed above was removed from the permeator and subjected to hydration (pre-treatment with water vapor outside the permeator) by placing the membrane in a box containing water at room temperature, atmospheric pressure and a relative humidity higher than 95%, e.g., 99%, until it reached a saturated state with water (humidified membrane).

[0093] 2.3 N 2 and H 2 Permeation test N2 and H2 permeation was carried out before and after humidification of Al-CMSM prepared as disclosed in Example 2, except for carbonization at 600°C. The effect of hydration was evident. Both N2 and H2 permeances were significantly decreased (see FIG. 5). However, the decrease in N2 permeance was larger than that of H2. This is reflected in the selectivity towards H2. Therefore, the ideal permeation selectivity of H2 / N2 at 1 bar for the humidified membrane is 70 times higher than that without humidification.

[0094] Example 3. Pretreatment of Al-CMSM inside the permeation chamber with water vapor Two molecular sieving carbon membranes were prepared as disclosed in Example 2, except for carbonization at 550° C. and 600° C. These were designated CMSM-550 and CMSM-600, respectively.

[0095] 3.1 Dry membrane The CMSM-550 and CMSM-600 membranes were placed inside the permeator. Nitrogen was then introduced into the permeator and the temperature was increased to 150° C. with a heating rate of 2° C. per minute. The mentioned temperatures were maintained for 6 hours to obtain the corresponding dehydrated membranes.

[0096] After desorption of water from the pores, the membrane was cooled to the permeation temperature (i.e., 20–100 °C) and permeation studies of the dry membrane were carried out.

[0097] 3.2 Humidifying membrane The dried membrane obtained above was exposed to a water-saturated N2 gas stream by bubbling the room temperature gas through a tank filled with water before feeding it into the permeation apparatus. To ensure consistent humidification conditions, the membrane was saturated with water from the humidification stream for 12 hours each night before the experiment. Pure nitrogen gas permeation tests were performed to confirm that the nitrogen permeation at a pressure of 4 bar was constant.

[0098] Example 4. Permeation studies of dry and humidified membranes Permeation of pure hydrogen and hydrogen-containing gas mixtures was carried out to measure hydrogen permeation and purity values ​​at various pressures and temperatures. Vacuum was used on the permeate side.

[0099] For the moist membranes, the first interesting result is the superior selectivity and permeability compared to the Robeson upper limit, as shown in Figure 6. This upper limit provides a benchmark against which new membrane materials can be compared.

[0100] The difference in hydrogen flux and purity for Al-CMSM (CMSM-550) carbonized at 550°C before (dry membrane) and after (humidified membrane) steam treatment of a gas mixture containing 50% hydrogen and 50% methane at 20°C and various hydrogen partial pressure differences is shown in Figures 7 and 8, respectively. Without wishing to be bound by theory, it is believed that the water treatment creates walls in the pores, resulting in a reduction in the pore size (pore filling). The results show that, despite a reduction in hydrogen flux (Figure 7), the hydrogen purity increases significantly (Figure 8).

[0101] Example 5. Permeation of gas mixtures using Al-CMSM-550 humidifying membrane Using the procedure described in Example 3, section 3.2, CMSM-550 was pretreated with a stream of N2 gas saturated with water vapor and used to measure hydrogen permeability and hydrogen purity in the permeate from binary mixtures of CH4, CO2, or N2 with hydrogen, with 10% hydrogen or 50% hydrogen, at various temperatures (20 °C to 70 °C) and with various partial pressure differences and with vacuum applied from the permeate side.

[0102] The separation of hydrogen present in a mixture with methane containing 10% hydrogen and 50% hydrogen was investigated using the CMSM-550 membrane. The hydrogen flux rates in the permeates obtained from a mixture of H2 and CH4 (10% hydrogen and 50% H2) at various temperatures and with various differences in the partial pressure of H2 are shown in Figure 9, and the correspondent H2 purity is shown in Figure 10. It can be observed that as the permeation temperature increases, the hydrogen permeance increases at the expense of the hydrogen purity. It is important to highlight that for carbon membranes saturated with water vapor, the hydrogen purity obtained is significantly higher, especially when a 10% H2 content is considered to be present in the mixture. Thus, in particular at 20°C at a hydrogen partial pressure of 0.55 bar, a purity of 97.5% is obtained.

[0103] Similar tests were performed for binary mixtures of N2 or CO2 with hydrogen, and the results for CO2 are shown in Figures 11 and 12, and for N2 in Figures 13 and 14.

[0104] For the separation of H2 from a mixture containing CO2, the permeate purity is less than that of CH4, possibly due to CO2 being smaller and more absorbent than CH4 (Figure 12).

[0105] In Figures 13 and 14, the H2-N2 results in terms of hydrogen flux and hydrogen purity are shown at different hydrogen partial pressure differences. High hydrogen purity was reached for all the different mixtures considered when the membrane was saturated with water. At higher temperatures, e.g. 100°C, an improvement in performance is indeed expected when the membrane is humidified.

[0106] For gases with notable differences in molecular size or very distinct adsorption capacities, such as CO2 / CH4 or CO2 / N2, similar results (to those obtained with H2 / N2, H2 / CH4, and H2 / CO2) are expected. Due to their high water adsorption capacities, membranes carbonized at 500°C-750°C, especially at 500°C-700°C, exhibit similar performances when tested in humidified conditions under dry gas. When operating with the corresponding humidified membranes, high selectivity and purity are expected to be reached up to operating temperatures of 100°C.

[0107] Thus, similarly, humidified Al-CMSM carbonized at 500°C was used to purify hydrogen from a mixture containing 10% H2 and 90% N2. This separation is important because it allows the hydrogen to be stored and distributed using the existing existing infrastructure of natural gas. For safety reasons, a low concentration of H2 (i.e. 10%) is allowed to be mixed. It was observed that the purity is highly dependent on the permeation temperature. In particular, at 30°C, the purity of the obtained hydrogen was 99.4%.

[0108] Example 6. Difference in hydrogen permeation properties of dry and humidified CMSM-600 membranes The membrane was heated at 150°C under nitrogen atmosphere in the permeation apparatus to obtain a dry CMSM-600 membrane (most of the water was removed from the pores).The temperature of the permeation apparatus was then cooled to 100°C, and hydrogen permeation of a mixture of 10% H2 and 90% CH4 at various hydrogen partial pressures was performed (100°C, dry membrane).

[0109] The same gas mixture was then saturated with water by bubbling it through water for 15 hours and placed in a permeation apparatus at 100° C. In this way, water was selectively adsorbed in the hydrophilic (humidified) membrane at 100° C., and hydrogen permeation was performed at various hydrogen partial pressures (100° C., humidified membrane). The same procedure was carried out at different temperatures, such as 70° C., 50° C., and 20° C.

[0110] Humidifying the membranes reduced the hydrogen flux (Figure 15) and led to a notable increase in purity (Figure 16). At higher temperatures, this was even more evident. The average increase in purity (humid vs. dry) that occurred after the membranes were humidified was 18% at 100°C, 14% at 70°C, 10% at 50°C, and only 4% at 20°C (Figure 17). This indicates that preconditioning of the carbon membranes with a water vapor flow is even more important at temperatures higher than 100°C.

[0111] Thus, the results show that humidifying the membrane offers significant advantages, especially for purification at higher temperatures.

[0112] Comparative Example 1. Pd-based membrane for Al-CMSM For hydrogen separation, Pd-based membranes are used due to their high hydrogen permeability and exclusive selectivity. The permeation is preferably carried out at 400°C, because Pd-based membranes can be damaged at temperatures below 300°C and above 500°C.

[0113] In Pd-based membranes, the hydrogen flux is a function of the square root of the partial pressure difference across the membrane (Sieverts' law). In Al-CMSM, the flux is proportional to the partial pressure difference.

[0114] Figure 18 shows an example of the dependence of pressure on the hydrogen flux of a Pd-based membrane and of an Al-CMSM humidified inside the reactor with water until saturated, considering that both have the same permeance at a pressure difference of 1 bar. It can be observed that at low pressures the fluxes in both cases are similar. Nevertheless, as the pressure increases, the increase in permeation is much higher for the Al-CMSM than for the Pd-based membrane. At low pressures, the H2 permeation of the Al-CMSM is about 10 times lower than a Pd-based membrane with the same thickness, and the selectivity is also lower for the Al-CMSM (as a practical matter, 20-40 times lower for the Pd-based membrane). Nevertheless, the permeation of the Al-CMSM can be performed at low temperatures (i.e., room temperature) and the Pd membrane at high temperatures (usually 400 °C).

[0115] Comparative Example 2: Effect of hydrogen concentration in a mixture with other gases on hydrogen permeation Figure 19 shows the hydrogen permeation flux for pure hydrogen and various H2 / CH4 binary mixtures (100%-50% hydrogen) at 400 °C for a 1.29 μm thick PdAg supported membrane in function of the square root difference of hydrogen partial pressures (see Melendez, J. et al., "Preparation and characterization of ceramic supported ultra-thin (~1 μm) Pd-Ag membranes", J. Memb. Sci. 528 (2017), pp. 12-23). ​​Pure hydrogen follows Sieverts' law (linear dependence of H2 flux with the square root of the pressure difference), but as the concentration of hydrogen in the binary mixture decreases, the flux is not linear but shows a downward convexity towards the pressure axis. Due to the fact that partial pressures are used, already including the effect of dilution, and that CH4 can be considered inert, mass transport limitations from the bulk of the binary mixture to the membrane surface (concentration polarization) are the most likely explanation for this decrease, which becomes even more important for high flux highly selective membranes. Similar behavior was observed for a 2.5 μm thick supported membrane with 0.8 Pd and 0.2 Ag.

[0116] The results of hydrogen flux (Figure 20) and purity (Figure 21) for different mixtures of H2-CH4 with hydrogen concentrations from 10% to 70% are shown. A 20 cm Pd-Ag ceramic support membrane was used for the above mentioned tests. The trends were compared similarly to the pure gas tests. The retentate pressure was varied from 8 bar to 40 bar, while the permeate pressure was maintained at 0.15 bar using a vacuum pump. The hydrogen permeance was significantly reduced due to concentration polarization, especially when operating at low hydrogen contents. Similarly, the purity was significantly lower when comparing that obtained with pure H2. The reason for this could be the higher impurity concentration near the membrane surface due to the higher hydrogen permeability.

[0117] In Figure 22, we show the hydrogen permeation of binary mixtures of H2 / N2, H2 / CO2 and H2 / CH4 in function of H2 content at 400 °C and 3 bar total pressure (vacuum on the permeate side) for a PdAg supported membrane (see Melendez J. et al. 2017). It is clearly known that if the hydrogen concentration in the source decreases, the hydrogen permeation rate also decreases. Moreover, the permeated hydrogen flux decreases quite linearly from 100% to 0% H2 and is quite similar for the different H2 mixtures.

[0118] Example 7. Dependence of partial pressure difference and hydrogen flux in water-saturated Al-CMSM The hydrogen flux as a function of hydrogen partial pressure difference was tested at 20 °C for various H2 / CH4 and H2 / N2 mixtures and Al-CMSM (CMSM-550) carbonized at 550 °C after exposure to ambient humidity. The dependence of hydrogen partial pressure difference and hydrogen flux was found to be approximately linear, independent of the concentration of H2 in the mixture and tested gases (Figure 23), proving that concentration polarization does not affect the H2 flux of the membrane.

[0119] Results and Advantages of the Water-Saturated Al-CMSM of the Invention

[0120] The effect of water adsorbed on the membrane was also tested on Al-CMSM carbonized at 600 °C. First, water was removed by heating at 150 °C under N2, and permeation tests with dry and humidified gases were carried out to study the effect of treatment with water vapor on the purity of the permeated gas. This test was carried out for H2 / CH4 mixtures containing 10% H2 at various temperatures (20 °C, 50 °C, 70 °C and 100 °C) with various partial pressures of H2 to evaluate the relative increase in purity obtained under humidified conditions. The membrane showed a clear improvement in performance, especially after humidification at high temperatures.

[0121] Similar effects are expected for H2 / CH4, H2 / N2, H2 / CO2, CO2 / CH4, and CO2 / N2 gas mixtures due to the adsorption of water on the pore walls, which is more absorbent and promotes the permeation of smaller molecules.

[0122] Therefore, the water-saturated Al-CMSM shows promising performance compared to commercial membranes for gas mixture separation, especially at high pressure, due to the absence of mass transport limitations. Moreover, further improvement in gas purity, especially at high temperatures, is realized due to water adsorption when operated under humidified conditions.

[0123] As can be seen from Comparative Example 1 and Comparative Example 2 and the above examples, the water-saturated Al-CMSM of the present invention is advantageous for the following reasons. - Water saturated Al-CMSM offers significantly higher purity compared to dry Al-CMSM, especially at high temperatures. H2 permeation over -Pd membranes is carried out at 300°C to 500°C, whereas Al-CMSM can be carried out at room temperature, and therefore, considering similar permeability, the operating costs are lower for Al-CMSM. While the -Pd-based membranes are very expensive, the Al-CMSM are made from a very inexpensive phenolic resin. The flux in the -Pd membrane is ΔP 0.5 While the H flux in the Al-CMSM depends on ΔP, the H flux in the Al-CMSM depends on ΔP. Thus, the H flux at high pressure and low temperature is higher in the Al-CMSM. - In the permeation of mixed gases, for the Pd membrane, the hydrogen flux decreases as the H2 concentration decreases, whereas for the Al-CMSM, the flux remains almost constant (not due to concentration polarization).

[0124] Example 8. Carbon membrane for water vapor permeation In water permeation, concentration can occur depending on the water pressure and temperature, resulting in the presence of both monolayer adsorbed water and free water (gas) (Figure 24). Water in the pores increases with increasing pressure and decreasing temperature.

[0125] Effect of carbonization temperature on water permeation As explained above, it is possible to modify the hydrophilicity of the carbon membrane by changing the carbonization temperature. For the Al-CMSM of example 2.2, the water permeance was measured at different temperatures and a pressure difference of 3 bar. This is shown in Figure 25. Independent of the carbonization temperature, the lowest permeance was obtained when the experiment was carried out at 150 °C. As already explained, this is due to the condensation of water in the pores. For the membranes carbonized at 500 °C and 550 °C, the highest permeance was obtained at a permeation temperature of 200 °C. For the membranes carbonized at 600 °C and 650 °C, the maximum of the permeation temperature shifted to 250 °C (Figure 25). When the carbonization temperature of the membrane was increased to 750-850 °C, the permeance peak shifted again to 200 °C.

[0126] The permeation peak was associated with the hydrophilicity of the pores. Without wishing to be bound by theory, as the carbonization temperature increases from 550 to 600°C, the number and size of the pores increases, exposing them to more hydrophilic groups, and the number of active molecules that react with water also increases to form new hydrophilic groups. As the temperature increases from 650°C, the hydrophilic groups are removed and condensation reactions occur between the activated carbons, reducing the porosity of the membrane and thus reducing the water permeability. This is evident for the membrane carbonized at 850°C. Thus, the water permeance at this temperature is lower than that at 750°C. With more hydrophilic groups present in the pores, water can bind more tightly to the pores and requires more energy (higher temperature) to remove them.

[0127] Ideal water / gas permeation selectivity For the Al-CMSM of Example 2.2, the permeance of various gases (N2, H2, CH4, CO, CO2) at different temperatures was measured, and their ideal water / gas selectivity (i.e., water permeation selectivity) was calculated. The results are shown in Figure 26. For the gases tested, all the membranes showed selectivity to water. This is because this membrane has the smallest kinetic diameter (0.26 nm, molecular sieving movement) and has a higher affinity to the pores (adsorption-diffusion transport).

[0128] The water permeation selectivity depends on the carbonization temperature and the permeation temperature.

[0129] The highest selectivity was obtained when the permeation was carried out at about 200°C, regardless of the carbonization temperature, with the exception of the mixture H2O / N2, which in this case obtained a maximum value at about 250°C for the membrane carbonized at 750°C. Presumably, around this carbonization temperature, the number and size of the pores are the best for water permeation, below this temperature there are fewer pores, and above this temperature water starts to condense in the pores, reducing the porosity, hydrophilicity and pore size. In fact, the membrane carbonized at 1000°C obtained the lowest selectivity.

[0130] In general, for the gases tested, the highest selectivity is obtained with the membrane carbonized at 750°C.

[0131] FIG. 26 shows the ideal selectivity of water / gas in function of kinetic diameter and permeation temperature for Al-CMSM of Example 2.2 carbonized at different temperatures. For all carbonization temperatures, the highest selectivity is obtained for water / N2. The water selectivity for CO2 and H2 is lower than N2, which can be attributed to the larger kinetic diameter of the latter. CO, which is larger than N2, has a lower selectivity. CO is a polar compound that can be adsorbed on the hydrophilic pores of the carbon membrane, which increases the adsorption-diffusion mechanism of permeation. Comparing CO and CH4, CH4 is larger than CO, so the permeation is lower. Considering N2 and CH4, CH4 is a symmetric molecule and cannot be easily polarized. Meanwhile, N2 is less symmetric and can be more easily polarized by increasing the dipole-induced dipole interaction with the polar pores.

[0132] The lowest selectivity was observed for H2 because its molecular size is slightly larger than that of water, and in addition, water can form hydrogen bonds with the pores to increase the adsorption-diffusion permeation.

[0133] References 1.Llosa MA et al.´´Composite-alumina-carbon molecular sieve membranes prepared from novolac resin and boehmite.Part I:Preparation,characterization and gas permeation studies´´,Int.J.Hydrogen Energy.2015,vol.40,pp.5653-5663. 2.M.A.Llosa et al.´´Composite-alumina-carbon molecular sieve membranes prepared from novolac resin and boehmite.Part II:Effect of the carbonization temperature on the gas permeation properties´´,Int.J.Hydrogen Energy.2015,Vol.40,pp.3485-3496. 2.Campo MC et al.´´Carbon molecular sieve membranes from cellophane paper´´Journal of Membrane Science,2010,vol.350,pp.180-188; 3.Teixeira M et al.´´Composite phenolic resin-based carbon molecular sieve membranes for gas separation´´,Carbon 2011,vol.49,pp.4348-4358; 4.Teixeira M et al.´´Carbon-Al2O3-Ag composite molecular sieve membranes for gas separation´´ Chem.Eng.Res Des.2012,vol.90,pp.2338-2345. 5.Rodrigues SC,et al.´´Preparation and characterization of carbon molecular sieve membranes based on resorcinoleformaldehyde resin´´ J.Memb.Sci.2014,vol.459,pp.207-216. 6.Nguyen C.,Do,DD´´Adsorption of supercritical gases in porous media:determination of micropore size distribution´´.J.Phys.Chem.B.1999,103(33),6900-8,and 7.Nguyen C et al.´´The structural characterization of carbon molecular sieve membrane(CMSM)via gas adsorption´´ J.Memb.Sci.,2003,220(1-2)177-82. 8.Melendez J et al.,´´Preparation and characterization of ceramic supported ultra-thin(~1μm)Pd-Ag membranes´´, J.Memb.Sci.2017,vol.528,pp.12-23.

[0134] For reasons of completeness, various aspects of the invention are described in the following numbered paragraphs. 1. A water-saturated molecular sieving carbon membrane, a) providing a hydrophilic molecular sieving carbon membrane (CMSM) comprising pores with a pore size of 0.25 nm to 0.55 nm for molecular sieving, and pores with a pore size of greater than 0.55 nm to 0.90 nm for adsorption-diffusion, and a negligible amount of pores greater than 0.90 nm, wherein a plot of N2 permeance versus permeation pressure at room temperature and a pressure of 1 to 4 bar has a zero or negative slope, and the CMSM has a negligible amount of pores greater than 0.90 nm; b) humidifying the membrane until a water-saturated molecular sieving carbon membrane is obtained. 2. 2. The water-saturated molecular sieving carbon membrane of claim 1, wherein the CMSM is a molecular sieving alumina-carbon composite membrane (Al-CMSM). 3. 3. The water-saturated molecular sieving carbon membrane of claim 2, wherein the Al-CMSM has a nitrogen content of 0.1 wt.% to 4.0 wt.%, an alumina content of 2.5 wt.% to 50 wt.%, and a carbon content of 50 wt.% to 95 wt.%, based on the total weight of the membrane. 4. 1. A process for separating a gas from a gas mixture, comprising: a) providing a water-saturated membrane as defined in any one of clauses 1 to 3; b) providing a gas mixture comprising at least two gases; c) feeding a gas mixture to a water-saturated CMSM at a temperature between 5°C and 300°C to obtain a retentate and a permeate, wherein the partial pressure of the gas in the retentate is higher than the partial pressure of the gas in the permeate; and feeding, which is carried out at a pressure such that the membrane is still water saturated. 5. 5. The process of claim 4, wherein the temperature in step (c) is from 5°C to 250°C, from 5°C to 120°C, from 15°C to 120°C, from 15°C to 100°C, from 15°C to 70°C, or from 20°C to 50°C. 6. At least two gases have polarizabilities between 2 and 27, and at least one of the at least two gases has a kinetic diameter less than 0.55 nm, and if at least two gases have a kinetic diameter less than 0.55 nm, the difference in kinetic diameter between the at least two gases is 0.01 nm or more, and / or the difference in polarizability between the at least two gases is 1 m. 3 The process according to clause 4 or 5. 7. 7. The process of claim 6, wherein the at least two gases are selected from He, H2O, Ne, H2, NO, Ar, NH3, N2, O2, CO, CO2, CH4, C2H4, C2H6, propene, propane, H2S, methanol, and ethanol. 8. 8. The process of any one of clauses 4 to 7, wherein the gas mixture comprising at least two gases is selected from the group consisting of H2 / CH4, H2 / N2, H2 / CO2, CO2 / CH4, CO2 / N2, O2 / N2, and biogas. 9. 9. The process according to clause 8, wherein the gas mixture comprises 5%-20% H2 and 95%-80% CH4, and step c) is carried out at a hydrogen partial pressure difference of 3 bar or more and at a temperature of 40° C. or less. 10. 9. The process according to clause 8, wherein the at least two gases are CO2 and N2, and the gas mixture comprises 10%-20% CO2 and 65%-75% N2, in particular about 15% CO2 and 70% N2. 11. 9. The process according to clause 8, wherein the at least two gases are H2 and CO2, and the gas mixture comprises 55%-65% H2 and 30%-40% CO2, in particular about 60% H2 and 35% CO2. 12. 9. The process of claim 8, wherein the gas mixture comprising at least two gases is biogas and CO2 is removed from the biogas. 13. Use of a water-saturated CMSM as defined in clauses 1-3 to separate a gas from a gas mixture. 14. Use of water-saturated CMSM as defined in clauses 1-3 to dehydrate the solvent. 15. Use of a water-saturated CMSM as defined in clauses 1-3 as a membrane reactor.

Claims

1. A water-saturated molecular sieving carbon membrane, i) pores with a pore size of 0.25 nm to 0.55 nm for molecular sieving, and pores with a pore size of greater than 0.55 nm to 0.90 nm for adsorption diffusion, with a negligible amount of pores larger than 0.90 nm, resulting in a N 2 providing a hydrophilic carbon molecular sieving membrane (CMSM) having a permeance plot with a zero or negative slope; ii) humidifying the CMSM obtained in step i) to obtain water saturated CMSM, - subjecting the CMSM to a humidification treatment with water vapor at a temperature between 5°C and 180°C, at atmospheric pressure and at a relative humidity higher than 95%, for a defined period of time, such that after the humidification treatment with water vapor, the permeation flux of the non-adsorbable gases N2 or He is constant for 3 hours at 4 bar and at the temperature at which the CMSM was humidified with water vapor, or - The CMSM is mixed with water-saturated N 2 or He gas flow, the water-saturated N 2 or He gas flow being obtained by bubbling N 2 or He gas through a tank filled with water, 2 or He gas flow, treating the CMSM such that the permeation flux of non-adsorbable gases N2 or He is constant for 3 hours at 4 bar and at a temperature between 5°C and 180°C; to obtain water saturated CMSM by A water-saturated molecular sieving carbon membrane obtained by the above process.

2. 2. The water-saturated molecular sieving carbon membrane of claim 1, wherein the CMSM is a molecular sieving alumina-carbon composite membrane (Al-CMSM).

3. 3. The water-saturated molecular sieving carbon membrane according to claim 2, wherein the Al-CMSM has a nitrogen content of 0.1 wt % to 4.0 wt %, an alumina content of 2.5 wt % to 50 wt %, and a carbon content of 50 wt % to 95 wt %, based on the total weight of the membrane.

4. A process for preparing water-saturated molecular sieving alumina-carbon composite membrane (water-saturated Al-CMSM), comprising: i) preparing a hydrophilic Al-CMSM, -Porous α-Al 2 O 3 Providing a support; - preparing a solution containing 5-20 wt% phenol formaldehyde resin, 0.5-5 wt% formaldehyde, 0.1-2 wt% ethylenediamine, 0.1-5 wt% boehmite in N-methyl-2-pyrrolidone, and heating said solution to perform a prepolymerization process to obtain a coating solution; - in said coating solution to obtain a coated support, 2 O 3 dip coating the substrate; - drying the coated substrate at a temperature between 70 and 120°C to complete the polymerization process; carbonizing the dried coated support at a carbonization temperature of 450° C. to 750° C. to obtain Al-CMSM; preparing hydrophilic Al-CMSM by ii) humidifying the Al-CMSM prepared in step i) to obtain water saturated Al-CMSM, - treating the Al-CMSM with water vapor for a defined period of time at a temperature between 5°C and 180°C, at atmospheric pressure and at a relative humidity higher than 95%, such that after the treatment with water vapor the permeation flux of the non-adsorbable gases N2 or He is constant for 3 hours at 4 bar and at the temperature at which the Al-CMSM was treated with water vapor; or - Water saturated N 2 exposing the Al-CMSM to a N2 or He gas stream, the N2 or He gas stream being saturated with water, obtained by bubbling the N2 or He gas through a tank filled with water, such that the permeation flux of non-adsorbable gases N2 or He is constant for 3 hours at 4 bar and at temperatures between 5°C and 180°C after exposure to the N2 or He gas stream saturated with water; obtaining water saturated Al-CMSM by Preparation process of water-saturated molecular sieving alumina-carbon composite membrane.

5. 5. The process of claim 4, wherein the phenol formaldehyde resin is a novolac resin.

6. 6. The process according to claim 4 or 5, wherein the carbonization temperature is between 450°C and 700°C.

7. A water saturated Al-CMSM obtainable by the process defined in any one of claims 4 to 6.

8. 1. A process for separating a gas from a gas mixture, comprising: a) providing a water-saturated membrane as defined in any one of claims 1 to 3 or claim 7; b) providing a gas mixture comprising at least two gases; c) feeding said gas mixture to said water saturated CMSM at a temperature between 5°C and 300°C to obtain a retentate and a permeate, said process being carried out at a pressure such that the partial pressure of the gas in the retentate is higher than the partial pressure of the gas in the permeate and a difference in permeation is observed when compared to a process with a CMSM that has not been subjected to a humidification step.

9. The at least two gases have polarizabilities between 2 and 27, and at least one of the at least two gases has a kinetic diameter less than 0.55 nm, and if the at least two gases have a kinetic diameter smaller than 0.55 nm, the difference in the kinetic diameter between the at least two gases is 0.01 nm or more, and / or the difference in the polarizability between the at least two gases is 1 m. 3 The process of claim 8.

10. The at least two types of gases are He, H 2 O, Ne, H 2 , NO, Ar, NH 3 , N 2 , O 2 , CO, CO 2 , C.H. 4 , C 2 H 4 , C 2 H 6 , propene, propane, H 2 10. The process of claim 9, wherein the solvent is selected from S, methanol, and ethanol.

11. The gas mixture containing at least two gases is H 2 / CH 4 , H 2 / N 2 , H 2 / CO 2 , CO 2 / CH 4 , CO 2 / N 2 , O 2 / N 2 , and mainly methane and carbon dioxide, and H 2 , H 2 S.N. 2 11. The process according to any one of claims 8 to 10, wherein the biogas is a gas mixture containing methane and carbon dioxide, and other gases such as water vapor in smaller amounts.

12. The gas mixture is 5% to 20% H 2 , and 95% to 80% of CH 4 12. The process of claim 11, wherein step c) is carried out at a hydrogen partial pressure difference of 3 bar or more and at a temperature of 40° C. or less.

13. The at least two gases are CO 2 and N 2 and the gas mixture is 10% to 20% CO 2 and 65% to 75% N 2 The process of claim 11 , comprising:

14. The at least two gases are H 2 and CO 2 and the gas mixture is 55% to 65% H 2 and 30% to 40% CO 2 The process of claim 11 , comprising:

15. The gas mixture containing at least two gases is biogas, and 2 12. The process of claim 11 , wherein said biogas is a gas mixture comprising methane and carbon dioxide.

16. Use of water-saturated CMSM as defined in claims 1-3 or water-saturated Al-CMSM according to claim 7 for dehydrating a solvent.

17. Use of water-saturated CMSM as defined in claims 1 to 3 and water-saturated Al-CMSM according to claim 7 as a membrane reactor.

Citation Information

Patent Citations

  • Carbon film and method for producing the same

    WO2009150903A1